THE RELEVANCE OF IMPROVING THE MANAGERIAL ROLE OF A PHARMACY ORGANIZATION IN THE FORMATION OF ORGANIZATIONAL CULTURE - Петров, Андрей Георгиевич; Филимонов, Сергей Николаевич; Хорошилова, Ольга Владимировна; Сашко, Юлия Александровна; Семенихин, Виктор Андреевич; Григорьева, Елена Борисовна (Medicine in Kuzbass, 2023)
The review examines the relevance of improving the managerial role of a pharmacy organization in the formation of an organizational culture that increases competitiveness and reduces risk events. The personal characteristics of the manager as factors that increase competitiveness are shown. It is presented that the leading direction in the organizational culture of a pharmacy organization is the involvement of employees, showing the degree of participation of pharmacy employees in the organization’s activities, a positive attitude to their work, which leads to a reduction in risk events.